Determination of Acute and Chronic Exposure to Carbon Monoxide by Spectrophotometric Methods - Vural, Nevin; Yücesoy, Cem; Kahraman, Rukiye Doğanyiğit (The Bulletin of Legal Medicine, 1996)
COHb levels in the blood samples of victims of suspected CO poisoning (n: 18) and subjects exposed to low CO (smokers n:100, nonsmokers n:44) were measured by spectrophotometric methods. Derivative UV-spectrophotometric method was also used for the determination of COHb in the blood of smokers. The sensitivity and reliability of these methods were compared. COHb levels of postmortem blood samples were found to be between 63.00 ( 88.00 % (mean 73-11 % ( 6.90). COHb levels of 1-9 cigarettes smokers daily (n=44) were found to be 1.94 ( 0.11 % COHb; 3.25 ( 0.19 % COHb in smokers (10- 20 cigarettes daily, n=23). COHb level in all smokers (4.36 (0.14 %) were found significantly higher then the nonsmokers (p < 0.01, p < 0.05). Dubowski’s method for the quantati- ve estimation of the CO poisoning was evaluated as a sensitive and economic method among the spectrophotometric methods. Also it was shown that this method can be used easily in Forensic Medicine Laboratories as well as the procedure takes a short time. Key words: Carbon Monoxide, Carboxyhemoglobin, Acut Poisoning, Chronic Poisoning, UV Spectrophotometry, Derivative UV Spectrophotometry